Climate change will exacerbate seasonal flow variability in the Karnali River Basin: implications for water, energy, and agriculture sectors - Pradhananga, Saurav; Nepal, Santosh; Kamal, S. K.; Hafeez, Mohsin (IWA Publishing, 2025)
Climate change impacts water resources in the Himalayan region, with cross-sectoral effects felt across various scales. This study focuses on the Karnali River, which is crucial for livelihoods, agriculture, and hydropower generation in the region, and assesses the impact of climate change on these sectors. We use the SWATþ hydrological model with bias-corrected high-resolution CMIP6 projections to simulate future hydrology. Winter and spring discharge is projected to decrease by 3 (SSP245) to 23% (SSP585), while monsoon and post-monsoon discharge may increase by up to 18 (SSP245) and 51% (SSP585) by the end-century, primarily due to precipitation changes. Wet energy production from the Upper Karnali hydropower project is likely to increase, whereas dry energy may decrease, reducing overall reliability. The highest wet energy increase (9%) occurs under SSP585’s cold-wet scenario, while the largest dry energy decline (16%) is under SSP245’s warm-dry scenario by the end-century. Irrigation water requirements for paddy and wheat are also expected to increase, with paddy’s initial growth stage potentially doubling under warm-dry SSP585 conditions by the end-century. Our findings highlight the need for integrated water, food, and energy management strategies in the Karnali River basin to address the cross-sectoral impacts, particularly considering climate change challenges.